2008
DOI: 10.1364/josaa.25.003051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhomogeneous myofibril morphology on optical diffraction in single muscle fibers

Abstract: Laser diffraction is commonly used in physiological research that explores single muscle fibers. Although variations in sarcomere morphological properties have often been observed, their effects on laser diffraction have not been studied in detail. In this study, we applied three-dimensional coupled wave theory to a physical sarcomere model to investigate the effects of inhomogeneous morphological profiles in muscle fibers. The simulation results were compared with several those of published experimental studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…3d and e), approximately 2-3 times larger than for the longitudinal muscle. The lower lasing threshold in the longitudinal muscle is due to the light-guiding (light confinement) mechanism along the myofribils myofibrils 51,52 (see Fig. S6 to visualize the light-guiding effect) and fewer interfaces (myobribril/sarcolemma) that the light encounters when it travels between the two mirrors.…”
Section: Resultsmentioning
confidence: 99%
“…3d and e), approximately 2-3 times larger than for the longitudinal muscle. The lower lasing threshold in the longitudinal muscle is due to the light-guiding (light confinement) mechanism along the myofribils myofibrils 51,52 (see Fig. S6 to visualize the light-guiding effect) and fewer interfaces (myobribril/sarcolemma) that the light encounters when it travels between the two mirrors.…”
Section: Resultsmentioning
confidence: 99%
“…21 This phenomenon suggested light propagation behavior in muscle was different from that in fibrous samples. Because the periodic sarcomere structure is the most distinct feature of striated muscles comparing with nonmuscle fibrous tissues, the strong sarcomere diffraction 22 most likely have played certain roles in modulating light propagation in skeletal muscle.…”
Section: Spatial Profiles Of the Transmittance Imagesmentioning
confidence: 99%
“…21 On the other hand, the incident light may also be diffracted by the periodic sarcomere structure to directions that were parallel to the fiber orientation. 22 These two competing effects likely "stretched" the transmitted light along both the x-and y-axis, resulting in the patterns shown in thin samples. Our previous calculation has shown that the periodic sarcomere structure 13 diffracts much less V-polarized light along the muscle fibers than H-polarized light.…”
Section: Spatial Profiles Of the Transmittance Imagesmentioning
confidence: 99%